Natural gas in Latin America and interactions with the rest of the world - Honoré, A (Oxford Institute for Energy Studies, 2015)
Latin America has long been disconnected from other gas markets, focusing instead on regional integration via pipeline – especially in the Southern Cone. In the mid-2000s, a shortage of natural gas production coupled with political disagreements, tensions over price renegotiations, and shortfalls of deliveries from neighbours led several countries to turn to LNG imports – either to replace or supplement indigenous production and imports of pipeline gas. From 2009, the region has gone from being a closed regional market, with only regional pipeline flows, to a region that both imports and exports LNG. (In this article, Latin America includes 10 countries: Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Paraguay, Peru, Uruguay and Venezuela.)